Coercive control and risk in intimate partner violence: are Canadian police prepared to assess? - Aspinall, Mary (Policing and society, 2024)
Coercive control is an ongoing pattern of abuse that is intended to isolate, humiliate, degrade, and micro-regulate the everyday life of a victim; often found amongst intimate partner violence (IPV) situations yet may not present with physical evidence. Police officers are called to respond to these conditions, yet are limited by training, legislation, and risk assessment tools that often concentrate primarily on the presence of physical violence alone. An online survey was distributed to police officers across Canada to understand how they explore, and respond to IPV and coercive control, and what they consider to be the most pertinent risk factors when assessing the severity of a situation. Findings reveal that police officers continue to emphasise perpetrator behaviours that involve physical violence and serious physical harm. As Canada is currently considering the possibility of criminalising coercive control, results highlight that further training and improved risk assessment tools will be necessary in order for police to be able to effectively respond.